Perspective on Religious Moderation of Ptkin Students in the Post Truth Era (Case Study on Students of al-Quran and Tafsir Science Study Program Uin Khas Jember) - Palupi, Anggi (Advances in Humanities and Contemporary Studies, 2024)
Information and communication technology which has developed massively has resulted in technological disruption, so that today’s society can easily and quickly obtain various information until a information floods emerges. Information in online media has power, both the power to build and the power to destroy. Especially those related to religion, can certainly be disturbing, especially for the younger generation or students. A wrong understanding of religion can be dangerous because it can lead to intolerance and even radicalization. In the end, the concept of religious moderation emerged. This article wants to know the perspective of PTKIN (state Islamic religious college) students in the Al-Qur’an and Tafsir Science Study Program at UIN KHAS Jember regarding religious moderation. The research method used a qualitative research with a case study approach. The data analysis technique used the Miles and Huberman model which consists of Data Collection, Data Reduction, Data Display, and Conclusion. The technique for determining informants was purposive, namely students of the 2020-2021 Al-Qur’an and Tafsir Science Study Program, UIN KHAS Jember. The results of the research show that students of the Al-Qur’an and Tafsir Science Study Program at UIN KHAS Jember already have a good perspective regarding religious moderation up to the highest domain stage, namely evaluation. This can be a good provision for students belonging to the Z generation, to be able to filter various temptations from the flood of information on social media which has a negative impact, especially on the growth of extremism and radicalism thought patterns.